2023
DOI: 10.3389/fpls.2023.1265971
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics and metabolomics association analysis revealed the responses of Gynostemma pentaphyllum to cadmium

Yunyi Zhou,
Lixiang Yao,
Xueyan Huang
et al.

Abstract: Gynostemma pentaphyllum an important medicinal herb, can absorb high amounts of cadmium (Cd) which can lead to excessive Cd contamination during the production of medicines and tea. Hence, it is crucial to investigate the response mechanism of G. pentaphyllum under Cd stress to develop varieties with low Cd accumulation and high tolerance. Physiological response analysis, transcriptomics and metabolomics were performed on G. pentaphyllum seedlings exposed to Cd stress. Herein, G. pentaphyllum seedlings could s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…Our previous research showed that salt stress would increase the content of two major active components of licorice, by increasing the expression of the synthetase gene of skeleton compounds and the downstream glycosyltransferase genes [6][7][8]. It is generally believed that many secondary metabolites of traditional Chinese medicine, i.e., active components, accumulate more under abiotic stress [9][10][11]. In addition, licorice species are capable of tolerating drought conditions [12,13] and, correspondingly, drought stress is also an important factor to promote the biochemical composition of licorice by regulating the synthesis genes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research showed that salt stress would increase the content of two major active components of licorice, by increasing the expression of the synthetase gene of skeleton compounds and the downstream glycosyltransferase genes [6][7][8]. It is generally believed that many secondary metabolites of traditional Chinese medicine, i.e., active components, accumulate more under abiotic stress [9][10][11]. In addition, licorice species are capable of tolerating drought conditions [12,13] and, correspondingly, drought stress is also an important factor to promote the biochemical composition of licorice by regulating the synthesis genes [14].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of metabolomics and transcriptomics (RNA-seq) has become an effective tool for studying and identifying post-genomic processes and the molecular basis of various plants [15]. The combined analysis of metabolomics and RNA-seq reveals the mechanisms and dynamic changes in the synthesis of diverse plant metabolic compounds, including Mesona chinensis [16], Plumbago zeylanica [17], Bupleurum chinense [18], and Gynostemma pentaphyllum [19].…”
mentioning
confidence: 99%